Асимптотические нелинейные уравнения равновесия оболочек с геометрическими несовершенствами при взаимодействии форм потери устойчивости - Жукова, Н.Б. (Видавничий дім "Академперіодика" НАН України, 2008)
The asymptotic equilibrium equations of shells with geometric imperfections which take the interaction of buckling modes in a neighborhood of the critical point into account are derived. This derivation is based on the principle of virtual works and a Timoshenko type theory of shells. The obtained system of equations can be used for the analysis of a nonlinear deformation of shells with imperfections in the prebuckling and initial postbuckling states.